27 Genomic relationship between antibody response to porcine reproductive and respiratory syndrome virus vaccination and reproductive performance in commercial sows. (30th November 2020) - Sanglard, Leticia P; Fernando, Rohan; Gray, Kent A; Linhares, Daniel C; Dekkers, Jack C; Niederwerder, Megan C; Serão, Nick V
Abstract: Antibody response, measured as sample-to-positive ratio (S/P), to porcine reproductive and respiratory syndrome (PRRS) after PRRS outbreaks has been proposed as an indicator trait to improve reproductive performance in PRRS-infected sows. However, waiting for a PRRS outbreak to occur and having different relationships in healthy pigs may limit the use of this trait. Thus, we proposed to investigate if this relationship also occurs between S/P to PRRS vaccination and reproductive performance in sows without exposure to PRRS. Nine hundred six F1 replacement gilts (139□17 days old) from two commercial farms were vaccinated with a commercial modified live PRRS virus vaccine. Blood samples were collected at 52 days after vaccination to measure S/P to PRRS and SNP genotyping. Reproductive performance included: number born alive (NBA), number of piglets weaned, number born mummified (MUM), number stillborn (NSB), and pre-weaning mortality (PWM) at parities (P) 1 to 3. Average performance was calculated for each trait per sow per year (PSY). Farrowing rate and age at first service were also analyzed. BayesC0 was used to estimate genetic correlations between S/P and reproductive performance. Bivariate genome-wide association studies of antibody response and reproductive traits were performed using BayesB. High genetic correlations between S/P and farrowing performance were identified for NBA_P1 (0.61±0.16), PWM_P2 (-0.64±0.15), PWM_P2 (-0.63±0.20), NSB_P3 (-0.84±0.05), MUM_P3 (-0.83±0.11), and NSB_PSY (-0.90±0.05). A QTL was identified on chromosome 7 (MHC region) for these reproductive traits and for S/P, explaining from 1.2% (PWM_P2) to 22.4% (S/P) of the genetic variance. SNP H3GA0020505 explained most of the variance in this region for these traits. Heterozygote animals for this SNP had overall better performance: greater S/P (P = 0.001), greater (P = 0.06) NBA_P1, and lesser (P = 0.06) MUM_P3 than other genotypes. These results suggest that antibody response to PRRS vaccination may be used as a genetic indicator to improve reproductive performance in commercial pigs.